Social construction on cultural multiculturalism - Sukamto Sukamto; I Nyoman Ruja; Agus Purnomo (Jurnal Teori dan Praksis Pembelajaran IPS, 2018)
This paper aims to disseminate the results of the study and get feedback about the "Social construction on Multiculturalism". Five years ago Ahimsa Putra states that the face of Indonesia as pluralism without multiculturalism. Until now the problem of multiculturalism has become something that must be kept alive in an attempt to minimize the incidence of national disintegration. Winter tried to rethink multiculturalism by taking a lesson from Canada, that Canada has experienced setbacks in implementing the work program of multiculturalism. While Pakulski looks at the implementation of multiculturalism policy program in Australia as a blur. Scuzzarello, with optimism, invites to care about multiculturalism and share power on different communities. Gozdecka (et al), in recent years after the multicultural declared, stated that it is a failure both in Europe and in Anglophone West. This study was conducted in Blitar, using a qualitative approach to data collection methods and also interviews with ten informants. As a result, the construction of the community regarding multiculturalism: they consider themselves as the brother. In addition they also describe that: (a) assert one's cultural identity, study and assess the cultural heritage of a person; (b) respect and desire to understand and to learn about (and from) cultures besides their culture; (c) assessing and were delighted with the difference in the culture itself, which saw that the presence of groups from different cultures in the community as a positive thing to be respected and maintained. The harmony was found both in everyday lives, especially in the Religious and National holidays, for example, Eid Al-Fitr, Vesak, Christmas, and others religious holiday. Other examples, it also happens during the commemoration of National Holiday such as the Independence Day, the Youth Pledge Day, and the others.DOI: 10.17977/um022v3i12018p059